Modification of heat moisture treatment (HMT) of sago and sweet potato starch for the diversification of dry noodle products - Shanti Fitriani; Yusmarini; Emma Riftyan; Erpiani Siregar; Mohamad, Nizaha Juhaida; Chairani, Shauma Fithra; Ayu, Nur Lidya (Hasanuddin University Food Science and Technology Study Program, 2025)
Sago starch and sweet potato starch, rich in carbohydrates, exhibit considerable potential as raw materials for dried noodle production. However, the functional limitations of native starches in food processing require modification, such as heat-moisture treatment (HMT). While HMT enhances starch functionality, the resulting starches exhibit low protein content, requiring supplementation with protein-rich ingredients such as mung bean flour. This study aimed to evaluate the potential of HMT-modified sago and sweet potato starches, combined with mung bean flour, for the diversification of dried noodle products. The initial findings revealed that HMT modification significantly improved the water-holding capacity, swelling power, solubility, and amylose content of the native sago starch. Pasting analysis indicated similar functional profiles for sago and sweet potato starches, with notable differences observed in HMT-treated sweet potato starch. A one-factor completely randomized design was employed, incorporating six treatments (P1R1, P1R2, P1R3, P2R1, P2R2, P2R3), where P1 represents HMT sago starch and P2 represents HMT sweet potato starch, combined with mung bean flour in ratios of R1 (100:0), R2 (70:30), and R3 (50:50). Each treatment was conducted in triplicates. The findings demonstrated that the treatments significantly enhanced elongation, water absorption, ash content, and protein content, while reducing the rehydration time and moisture content in the dried noodles. Among the formulations, P2R3 (a 50:50 ratio of HMT sweet potato starch to mung bean flour) emerged as the best treatment. This study highlights the potential of HMT-modified starches combined with protein-rich flour to develop nutritionally enriched and functionally superior dried noodle products.